The state of PSA counseling in male‐to‐female transgender patients in the U.S. Issue 14 (23rd June 2022) - Marthi, Siddharth; O'Rourke, Timothy K.; Tucci, Christopher; Pareek, Gyan; Hyams, Elias
Abstract: Background: Morbidity and mortality from prostate cancer (PCa) are known to vary heavily based on socioeconomic and demographic risk factors. We sought to describe prescreening PSA (prostate‐specific antigen) counseling (PPC) rates amongst male‐to‐female transgender (MtF‐TG) patients and non‐TG patients using the behavioral risk factor surveillance system (BRFSS). Methods: We used the survey data from 2014, 2016, and 2018 BRFSS and included respondents aged 40–79 years who completed the "PCa screening" and "sexual orientation and gender identity" modules. We analyzed differences in age, education level, income level, marital status, and race/ethnicity using Pearson's χ 2 tests. The association of PPC with MtF‐TG status and other patient characteristics was evaluated using multivariate logistic regression. Results: A total of 175, 383 respondents were included, of which 0.3% identified as MtF‐TG. Overall, 62.4% of respondents reported undergoing PPC. On univariate analysis, PPC rates were lower among MtF‐TG respondents when compared to the non‐TG group (58.3% vs. 62.4%, p = 0.03). MtF‐TG respondents were also more likely to report lower education level ( p < 0.01), lower‐income level ( p < 0.01), and were less likely to be white ( p < 0.01) than non‐TG respondents. However, multivariate analysis adjusting for these respondent features demonstrated an association between higher income and higher education levels with increased odds of PPC, but no association was demonstrated between MtF‐TG status and PPC rates. PPC rates for the MtF‐TG and non‐TG populations did not change significantly over time. Conclusions: Although PPC was less frequently reported among MtF‐TG respondents than in the non‐TG group on univariate analysis, this association was not demonstrated when controlling for confounders, including education and income levels. Instead, on multivariate analysis, low education and income levels were more predictive of PPC rates. Further research is needed to ensure equivalent access to prescreening counseling for patients across the socioeconomic and gender identity spectrum.